2012
DOI: 10.12816/0004895
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus among Viral Causes of Pediatric Respiratory Tract Infections at Benha University Hospital

Abstract: Background/Aim: Human bocavirus (HBoV) is a recently discovered parvovirus associated with acute respiratory tract infections in children. The aim of this study was to define the epidemiological profile and the clinical characteristics associated with HBoV infection in a population of children hospitalized with respiratory tract infections at Benha University Hospital, especially in terms of HBoV load. Methods: 200 nasopharyngeal aspirates were collected and analyzed at the period from September 2010 to July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…and Jiang et al . who found 10 and 8.85% incidences at Benha University in 2010–2011 [36] and at Children’s Hospital of Soochow University in 2013–2014, respectively [37]. Higher incidences (22, 56.8 and 15.4 %) were reported by Zaghloul et al .…”
Section: Discussionmentioning
confidence: 98%
“…and Jiang et al . who found 10 and 8.85% incidences at Benha University in 2010–2011 [36] and at Children’s Hospital of Soochow University in 2013–2014, respectively [37]. Higher incidences (22, 56.8 and 15.4 %) were reported by Zaghloul et al .…”
Section: Discussionmentioning
confidence: 98%
“…Abdel-Moneim et al ( 2016) used newly developed primers to increase the sensitivity of the PCR test for HBoV detection. Using these novel primers, the prevalence of HBoV was 56.8%, which significantly differs from previous and further studies conducted in Egypt, which found prevalence values of 22%, 10% and 18.2% respectively [12,13,17]. Abdel-Moneim et al explained that the high rate of prevalence of HBoV-1 was reported because of a potential nosocomial pathogen among pediatric care units.…”
Section: Discussionmentioning
confidence: 57%
“…HBoV is detected more frequently with other viruses in the respiratory and gastrointestinal tract (Table 2). HBoV co-infection is present at a high rate among the tested samples, especially with respiratory syncytial virus (RSV) [13,32,41], which is the most prominent virus that causes respiratory illness. However, there is a conflict regarding the role of HBoV in cases of co-infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation